The joy of family traditions : a season-by-season companion to celebrations, holidays, and special occasions - Thompson, Jennifer Trainer (Celestial Arts, 2008)
400 plus ideas for special occasions, holidays, and celebrations that can create family traditions. Includes major and minor American celebrations, from weddings to trips, to April Fool's Day, creating traditions for children, North American Christian and Jewish traditions, plus a few extras such as Cinco de Mayo, Chinese New Year, and Native American traditions.